Relation between obesity and depression in a sample of patients in Isfahan, Iran - Sheikhi, Ali (International Journal of Research in Medical Sciences, 2017)
Background:Obesity and depression are two widely spread problems which are associated with many other health problems and major public health implications. Because of their high prevalence and the fact that they are both associated with common health problems such as cardiovascular disease, diabetes mellitus, low bone mineral density and many others, a possible relation between obesity and depression has been tested repeatedly. In this study, the relationship between these two complications was examined among patients who visited the psychiatry department in Khorshid hospital in Isfahan, Iran. Methods:A cross-sectional study was conducted between 2006 and 2008 on patients in the psychiatry department in Khorshid hospital in Isfahan, Iran. The patients were interviewed by an experienced psychiatrist for the diagnosis of major depression. They were also interviewed by an experienced nurse for the collection of other relevant information. Results:1093 patients in total were examined during the study. The mean age (standard deviation) of the patients was 32.7 (12.6). 208 (18.8%) were diagnosed with major depression. 24.3% of patients with major depression were obese, versus only 13.8% of patients without major depression. Using a binary logistic regression model, major depression was associated with higher body mass index in men but not in women when other variables considered. Conclusion:These findings indicate that higher body mass index is associated with major depression, but this association is gender dependent. Further studies are needed to investigate the complexity of this relationship.